DIGITAL BASED PROJECT BASED LEARNING AS A NEW PARADIGM OF CONTEMPORARY ISLAMIC EDUCATION IN THE 21ST CENTURY - Shofi Aqidatul Izzah; Ahmad Sahidah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
The development of digital technology in the 21st century has required Islamic education to adapt to changing learning paradigms to remain relevant to the character of the modern generation. This study aims to analyze the implementation of digital-based Project-Based Learning (PjBL) in Islamic Education learning at Nurul Jadid Junior High School, Probolinggo, as a new paradigm for contemporary Islamic education. The method used was a qualitative case study, involving teachers, students, and guardians through interviews, observation, and documentation. Data analysis was carried out using the Miles and Huberman interactive model, and validation using triangulation and member checking. The results show that digital PjBL is able to build a collaborative, reflective, and authentic work-oriented learning culture. Digital products such as da'wah videos, educational podcasts, and infographics on Islamic values serve as a means of integrating knowledge and religious practice. This model also improves digital literacy, creativity, and student responsibility, while strengthening character and spiritual awareness. Thus, digital PjBL has proven to be a strategic approach in realizing 21st-century Islamic education that is globally competitive without losing its religious identity.